2023
DOI: 10.3390/ijms241310622
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Expression of Exosomal miR-92a-3p and miR-221-3p Could Predict the Response to First-Line Chemotherapy and Survival in Metastatic Colorectal Cancer

Abstract: The status of predictive biomarkers in metastatic colorectal cancer is currently underdeveloped. Our study aimed to investigate the predictive value of six circulating exosomal miRNAs derived from plasma (miR-92a-3p, miR-143-3p, miR-146a-5p, miR-221-3p, miR-484, and miR-486-5p) for chemosensitivity, resistance patterns, and survival. Thirty-one metastatic colorectal cancer patients were selected before receiving first-line irinotecan- or oxaliplatin-based chemotherapy. Blood samples were harvested at baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…It has been reported that miR-92a-3p promotes the occurrence and development of tumors in some malignant diseases. Furthermore, Xiao et al found that expression of exosomal miR-92a-3p could predict the response to first-line chemotherapy in colorectal cancer, as biomarkers, resonating with our observations in adenomyosis 21 .…”
Section: Discussionsupporting
confidence: 88%
“…It has been reported that miR-92a-3p promotes the occurrence and development of tumors in some malignant diseases. Furthermore, Xiao et al found that expression of exosomal miR-92a-3p could predict the response to first-line chemotherapy in colorectal cancer, as biomarkers, resonating with our observations in adenomyosis 21 .…”
Section: Discussionsupporting
confidence: 88%
“…Further studies on the underlying mechanisms of CRC initiation and progression are required to reduce mortality caused by this neoplasia. Undoubtedly, abnormal expression of miRNAs correlates with CRC pathological stage and prognosis [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Kjersem et al [ 133 ] evaluated miRNA expression in plasma samples from 24 metastatic CRC patients, discovering that 3 miRNAs (miR-106a, miR-484, and miR-130b) were significantly more expressed in non-responders than in responders to oxaliplatin-based treatments. Gherman et al [ 134 ] reported that elevated exosomal expression of miR-92a-3p and miR-221-3p might indicate resistance to first-line chemotherapy and was linked to shorter OS. A recent review highlighted various miRNAs that potentially influence 5-fluorouracil resistance, including miR10b, miR-19b, miR-20a, miR-21, miR-23a, miR-31, miR-34, miR-129, miR-140, miR-145, miR-192, miR-215, the miR-200 family, and miR-451 [ 1 ].…”
Section: Micrornasmentioning
confidence: 99%